2015
DOI: 10.1007/s10661-015-4391-z
|View full text |Cite
|
Sign up to set email alerts
|

Development of population structure and spatial distribution patterns of a restored forest during 17-year succession (1993–2010) in Pingshuo opencast mine spoil, China

Abstract: Afforestation of native tree species is often recommended for ecological restoration in mining areas, but the understanding of the ecological processes of restored vegetation is quite limited. In order to provide insight of the ecological processes of restored vegetation, in this study, we investigate the development of the population structure and spatial distribution patterns of restored Robinia pseudoacacia (ROPS) and Pinus tabuliformis (PITA) mixed forests during the 17 years of the mine spoil period of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
17
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(17 citation statements)
references
References 35 publications
0
17
0
Order By: Relevance
“…In our research, the tree diameter class distribution curves across all three forests suggested that trees in all forests were highly dense as saplings, but that mortality was also high ( Figure 3). It has been shown that initial clustering structure for juveniles was an important factor affecting adult spatial structure (Zhao, Wang, Bai, Pan, & Wang, 2015), but environmental heterogeneity also was an important factor (Myster & Pickett, 1992;Schurr, Bossdorf, Milton, & Schumacher, 2004 Zou, Liu, and Wang (2002), Zou, Cheng, and Lei (1998) and Lei, Wang, Guo, and Zhu (2007).…”
Section: Changes In Population Structurementioning
confidence: 99%
“…In our research, the tree diameter class distribution curves across all three forests suggested that trees in all forests were highly dense as saplings, but that mortality was also high ( Figure 3). It has been shown that initial clustering structure for juveniles was an important factor affecting adult spatial structure (Zhao, Wang, Bai, Pan, & Wang, 2015), but environmental heterogeneity also was an important factor (Myster & Pickett, 1992;Schurr, Bossdorf, Milton, & Schumacher, 2004 Zou, Liu, and Wang (2002), Zou, Cheng, and Lei (1998) and Lei, Wang, Guo, and Zhu (2007).…”
Section: Changes In Population Structurementioning
confidence: 99%
“…In remediation projects, fertile soil mixed with fragmented rocks is transported to form large-scale dumps [66]. The natural succession process of both soil and vegetation in these areas requires a significant amount of time, during which the dumps are exposed to wind and water erosion processes [67]. In this harsh environment, ecological rehabilitation needs to consider the restoration of potential-toxic-metal-polluted soil and the reconstruction of plant communities.…”
Section: Research Limitation and Future Workmentioning
confidence: 99%
“…Similarly, direct seeding is generally done in rows, with the same mix of seeds being applied at a constant rate over an area (Jonson ). As a result, revegetated communities often show uniform, linear, or random spatial arrangements, rather than the aggregated to random patterns more commonly observed in natural ecosystems (Miller et al ; Paton et al ; Zhao et al ). Revegetation also tends to have different relative abundances of species, fewer understory species, and greater admixture of species than natural systems (Lockhart et al ; Paton et al ; Schneemann & McElhinny ; Zhao et al ).…”
Section: Introductionmentioning
confidence: 99%